Kindergaten to High School: Navigating Leadership Multilevel Indonesian School of Jeddah - Sa'adah, Nur Maghfirotus; Thohir, Muhammad; Mardiyah, Mardiyah (Jurnal Administrasi Pendidikan Islam, 2024)
Multilevel leadership at Indonesian School of Jeddah is a managerial approach where the principal oversees several educational levels, ranging from kindergarten to high school, by distributing responsibilities in a structured manner. This concept emphasizes the importance of distributed leadership, collaboration between levels, and the empowerment of all organizational members, including teachers, staff, students, and the community. The implementation of multilevel leadership at Indonesian School of Jeddah is driven by the lack of human resources and the imbalance between the number of teachers and students at the school. This research is a qualitative descriptive study. The data collection methods include interviews and observations conducted over two months. The findings of this study indicate that the implementation of the multilevel leadership concept at Indonesian School of Jeddah is an effort by the principal to improve efficiency, encourage collaboration among school members, strengthen accountability, and develop leadership at every level, ultimately enhancing the quality of education at Indonesian School of Jeddah.